Prevention of alcohol related harm in the workplace – an exploratory study investigating the obstacles and facilitators of best practice - Velander, Fredrik (Curtin University, 2006)
Working life is a vital component of everyday life of men and women around the world; it provides us with money to pay for items such as food, clothes, rent, mortgages, and school fees and so on. It is also an important part in our socialisation process with other human beings, our thoughts and ideas are shaped during interaction with other people. But the workplace has throughout history has also had some negative impacts through poor working conditions. Coexistent with working life, alcohol has influenced social life throughout history and the positive and negatives related to alcohol use have been well documented. In medieval times it was believed that alcohol increased productivity, something that modern research has contradicted. Alcohol was often used as a means to cope with harsh physical working conditions. In the modern world more and more emphasis has focused on the psychosocial work conditions and issues such as stress and work-overload have become common items in the media. Drinking alcohol has become a remedy to many of these issues, and it is used to assist in relaxation from a stressful day at work. Research has focused on how to rehabilitate people and to monitor the direct or indirect negative effects connected to working life.Prevention on the other hand has been more or less overlooked for a long time. It is not until the last 15-20 years that more emphasis has been put on investigating the prevention of alcohol related harm in the workplace. The present study investigated the prevention of alcohol related harm in the workplace using a three step model divided into the following stages: a) a comprehensive critical literature review; b) interviews with leading prevention experts from English speaking nations; and c) interviews with managers and employees in white-collar private enterprises and government agencies. The factors that consistently showed up in each phase of the study as important for successful prevention were a solid evidence base, knowledge of the impact of alcohol on production and safety, a clear link between costs and benefits, comprehensiveness, transparency, culturally appropriate, involved employees and regular evaluation. What is desperately needed is a more consistent methodological approach in order to build a stronger evidence base in this field of research, to assist in the development of best practice in prevention of alcohol related harm in the workplace.